Jumlah Anak, Jarak Kelahiran Anak dan Peran Ayah dengan Kejadian Stunting Selama Pademi COVID-19 - Afnijar Wahyu; Laurena Ginting; Nelly Dameria Sinaga (Jurnal Keperawatan Silampari, 2022)
This study aims to examine the relationship between the number of children, birth spacing, and the father's role in the incidence of stunting during the COVID-19 pandemic. The research method uses quantitative research with a cross-sectional sampling approach. The results showed that the p-value on the variable number of children was 0.545 > 0.05, the birth spacing of children was 0.667 > 0.05, and the father's role was 0.771 > 0.05. In conclusion, there is no significant relationship between the number of children, birth spacing, and father's position with the incidence of stunting in children during the COVID-19 Pandemic in the Working Area of the Titi Papan Medan Health Center Keywords: Birth spacing, Number of Children, Father's Role, Stunting